Organic matter characteristics in a changing permafrost environment: Yukechi Alas landscape, Central Yakutia. - Windirsch, Torben; Grosse, Guido; Ulrich, Mathias; Schirrmeister, Lutz; Fedorov, Alexander N; Konstantinov, Pavel; Fuchs, Matthias; Strauss, Jens (PANGAEA, 2019)
These data are laboratory results for carbon characteristics (TOC, TC, TN, C/N ratio, stable carbon isotope ratio, radiocarbon ages from bulk organic material), sediment characteristics (mass specific magnetic susceptibility (4.65 kHz & 0.465 kHz), grain size measurements < 1 mm) and ice characteristics (sample mass (wet), sample mass (dry), absolute ice content, stable oxygen and hydrogen isotope ratios of pore ice, pH and conductivity of pore ice). Two cores were analyzed: Yedoma core YED1 N 61.75967° / E 130.47438°; h = 218 m asl total length: 22,35 m (recovery 21,13 m) ice wedge included from ~7,14 to ~9,5 m Alas core Alas1 drilled in the drained part of a thermokarst lake basin N 61.76490° / E 130.46503° total length: 19,80 m (recovery 11,14 m) unfrozen conditions from ~1,6 to ~7,5 m Both cores were drilled in March 2015 from dry land surface in a joint expedition of the ERC PETA-Carb poject and the DFG project UL426/1-1 "Short and long-term thermokarst dynamics due to climate changes and human impacts in Central Yakutia, Siberia (2013-2016)". The sample names are compiled as [campaign]-[core] [drive] [depth (top)] - [depth (bottom)]. Age calibration was done with Calib7.10. Grain size percentages were calculated using GRADISTAT (Blott and Pye, 2001). Missing carbon isotope and C/N ratio values are a result of carbon and/or nitrogen contents below detection limit (0.1 wt%). Missing ice characteristics values are a result of dry and/or fine material obstructing the pore ice/water extraction.
Organic material, sediment and ice characteristics of two permafrost cores from Yukechi Alas, Central Yakutia
Keywords: Alas; AWI_PerDyn; Carbon; Central Yakutia; Permafrost; Permafrost Research (Periglacial Dynamics) @ AWI; PETA-CARB; Rapid Permafrost Thaw in a Warming Arctic and Impacts on the Soil Organic Carbon Pool; Yedoma; Yukechi